ANALISIS FAKTOR KEBERHASILAN INSEMINASI BUATAN TERNAK SAPI POTONG DI KECAMATAN TOMBOLO PAO KABUPATEN GOWA - Amriana Hifizah; Astati Astati (Teknosains, 2015)
The enhancement of the implementation of ArtificialInsemination program is one of the government's efforts to boost thecattle’s population in Indonesia, especially the eastern part ofIndonesia. Gowa Regency through the Department of Fisheries andLivestock has been implementing Artificial Insemination (AI),especially in District of Tombolo Pao which has been running for 3years. This study was conducted to see how far the success rate of AIin District of Tombolo Pao by looking at the influence of severalfactors: the origin and quality of the frozen semen used, the farmers’characteristics, the inseminator qualifications, S/C ratio, ConceptionRate (CR) and Calving Interval (CI). This study was conducted fromJune to August 2014 in District of Tombolo Pao, Gowa Regency. Thebasic method used is descriptive and quantitative analysis. The dataused is primary and secondary data. This study aims to analyze thefactors that support the success of AI in District of Tombolo Pao,Gowa Regency, they are: The origin and quality of frozen semen used;Characteristics of the farmers; the Farmers’ participation on AI; andthe success of AI based on the score of Conception Rate (CR), S / Cratio, and Calving Interval (CI). Frozen semens used in AI in Districtof Tombolo Pao are from the Center of AI in Lembang and Singosari,West Java. The quality of the semen also can be determined from thescore of conception rate which is 60-75%. The characteristics of therespondent farmers: the majority age is 30-50 years (75%), most ofthe farmers’ background is elementary education level (70.5%), withthe main livelihood as farmers (79.6%) having averagely 4 -5 cattles(68.2%) and the average period of being a cattle farmer is 7-8 years(86.4%). Participation of farmers in the AI program is veryenthusiastic indicated by 79.5% of the farmers agree for crossingtheir cattle breed through AI technique. The period of the farming,number of livestock and the participation of the farmers in AIprogram is not significantly influenced the success of AI. However, thesuccess of AI program can be figured out through the score of CR =60-75% (84.1%); S / C ratio <3 (75%); and CI average of 12 months(70.5%). The age of the farmers is significantly influenced the success14 of AI in CI score (p <0.05). Level of education significantly influencedthe success of AI in CR score (p <0.05).